If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6a+9=45
We move all terms to the left:
6a+9-(45)=0
We add all the numbers together, and all the variables
6a-36=0
We move all terms containing a to the left, all other terms to the right
6a=36
a=36/6
a=6
| 5a−5=4a+4 | | 14-3a=-9a+7 | | 3(n+4)=2+4(n+1) | | 1/6y+4=-16 | | 2n+5=4n-15 | | x^+4x+3.5=0 | | 3/2(x-2)-5=-19 | | (y+3)^2=0 | | 4z+18=3z+2 | | 2+(-6)=x | | x(9-x)-2x(3-x)=3/7*7/3+x | | -6=-7+u | | y3=3y2-12y-18=0 | | 8×0=4n | | x/5-5/6=x/2+1/3 | | y/4+16=18 | | 13=7x-6 | | (2+5i)(2-5i)=0 | | 16-3(x+11)=x-3 | | 7-4z=2(2z+3) | | x/6+3=-3 | | |x-3|=6 | | -2-4=-5+c | | 4n-40=70(-2n+2) | | -7(x+5)-12=13+3 | | 5+(-4)=x | | 9y=6y=-12 | | x=1008÷3/4 | | 2(6+8k+k2)=0 | | 2p/7+36/7=6 | | 8p+6=3 | | (h+6)+4=2+h |